2015
DOI: 10.1146/annurev-biochem-060614-034206
|View full text |Cite
|
Sign up to set email alerts
|

Magic Angle Spinning NMR of Proteins: High-Frequency Dynamic Nuclear Polarization and 1H Detection

Abstract: Magic angle spinning (MAS) NMR studies of amyloid and membrane proteins and large macromolecular complexes are an important new approach to structural biology. However, the applicability of these experiments, which are based on (13)C- and (15)N-detected spectra, would be enhanced if the sensitivity were improved. Here we discuss two advances that address this problem: high-frequency dynamic nuclear polarization (DNP) and (1)H-detected MAS techniques. DNP is a sensitivity enhancement technique that transfers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 173 publications
1
104
0
2
Order By: Relevance
“…In a previous study conducted at 600 MHz (Fricke et al 2014), this system exhibited one of the best resolutions ever achieved for a protein sample under DNP conditions (Can et al 2015;Su et al 2015). Increasing the field strength to 800 MHz and using the biradical AMUPol (Sauvee et al 2013), the observed line-widths at half height are about 22 % smaller, improving the overall resolution of the spectrum sizably.…”
Section: Contentmentioning
confidence: 90%
“…In a previous study conducted at 600 MHz (Fricke et al 2014), this system exhibited one of the best resolutions ever achieved for a protein sample under DNP conditions (Can et al 2015;Su et al 2015). Increasing the field strength to 800 MHz and using the biradical AMUPol (Sauvee et al 2013), the observed line-widths at half height are about 22 % smaller, improving the overall resolution of the spectrum sizably.…”
Section: Contentmentioning
confidence: 90%
“…79 In particular, MAS NMR has provided information on backbone conformations, supramolecular organization, and registry of interstrand arrangements of amyloid fibrils. This has led to an atomic resolution structure of amyloid fibrils formed by a small peptide derived from transthyretin (TTR 105–115 ), which was determined utilizing a combination of MAS NMR spectra and cryo-electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 99% of carbon is 12 C with spin quantum number, I = 0 (NMR inactive) and 99.6% of nitrogen is quadrupolar ( 14 N) with I = 1, while only 1.1% ( 13 C) and 0.37% ( 15 N) are NMR active nuclei with I = 1/2. Therefore, there is a significant reduction of the sensitivity in ssNMR spectra of 13 There are many excellent research articles and reviews that highlight the role of fast 4 MAS for biomolecular NMR applications 21,23,25,26,27,28,29,30,31,32 .…”
Section: Introductionmentioning
confidence: 99%